Receptors for short-chain fatty acids in brush cells at the “gastric groove” - Eberle, Julia A.; Widmayer, Patricia; Breer, Heinz (Frontiers in Physiology, 2014)
In the stomach of rodents clusters of brush cells are arranged at the “gastric groove”, immediately at the transition zone from the non-glandular reservoir compartment to the glandular digestive compartment. Based on their taste cell-like molecular phenotype it has been speculated that the cells may be capable to sense constituents of the ingested food, however, searches for nutrient receptors have not been successful. In this study, it was hypothesized that the cells may express receptors for short-chain fatty acids, metabolites generated by microorganisms during the storage of ingested food in the murine forestomach, which lacks the acidic milieu of more posterior regions of the stomach and is colonized with numerous microbiota. Experimental approaches, including RT-PCR analysis and immunohistochemical studies, revealed that the majority of these brush cells express the G-protein coupled receptor types GPR41 (FFAR3) and GPR43 (FFAR2), which are activated by short-chain fatty acids. Both, the GPR41 receptor proteins as well as an appropriate G-protein, α-gustducin, were found to be segregated at the apical brush border of the cells, indicating a direct contact with the luminal content of this gastric region. The exposure of microvillar processes with appropriate receptors and signaling elements to the gastric lumen suggests that the brush cells may in fact be capable to sense the short-chain fatty acids which originate from fermentation processes during the retention of ingested food in the anterior part of the stomach.